Clinical and pathogenetic aspects of fever in patients with infectious diseases - K. V. Zhdanov; M. V. Yaremenko; Yu. P. Finogeev; S. M. Zakharenko (Журнал инфектологии)
About diagnostic valueof fever, in in fectious patients physicians knew from the time of Hippocrates. Significant contribution to thestudy madeby S. Libermeister, SP Botkin, AA Ostroumov, IP Pavlov, II Metchnikoff andothers. Themain centerof thermoregulation is the hypothalamus. The reare three sources of temperature reception – ther more ceptors of the skin, ther mose nsitive of inter oreceptor sand specific thermosensitiveneuronsof theCNS (neuronsnucleusanterior, middle and posteriorhy pothalamus). Ther more ceptors of the skin andthermal of interoceptorsarechannelswith transient receptorpotential (temperature-sensitivetransient receptorpotential (TRP) channels) of thefreenerveendings, such asthevagusnerve.Current experimental studiesshow that thereareseveral waysto initiatefever. Themain classical pathway of feverisassociated with increasedprostaglandin synthesisby theaction of endogenouspyrogens. Endogenouspyrogensincludea numberof cytokines: interleukin-1 (IL-1), interleukin-6 (IL-6), tumornecrosisfactoralpha (TNF-α); interferon (IFN). Themain secondary pyrogen isconsideredto beIL-1β. Synthesisof IL-1β stimulatedstructuresPAMPs(pathogen-associatedmolecularpatterns)andDAMRs(danger-associatedmolecularpatterns), dependson theactivation of caspase–1 with inflammasom. Thestateof thermoregulation andisnow estimatedthermometry. Thefounderoftheclinical thermometerisa German physician C. Wunderlich. Abroad,the«goldstandard» isa measurement of rectal body temperature, asthemost stableandreliable. In ourcountry, in practice, usually measuredaxillary body temperature. Accordingto thetypesof feverandtemperaturecurvesinfectiousdiseasescan predefinenosological formof infectiousdisease. Amonginfectiousdiseasesaremost common, andsometimesalmost pathognomonic (malaria), fora given nosological formof thereaction temperature.